MRI and luminescence detection of Zn2+ with a lanthanide complex–zinc finger peptide conjugate. Issue 53 (18th June 2018) - Isaac, Manon; Pallier, Agnès; Szeremeta, Frédéric; Bayle, Pierre-Alain; Barantin, Laurent; Bonnet, Célia S.; Sénèque, Olivier
Abstract : A zinc finger peptide provides an excellent scaffold for the design of lanthanide-based luminescent and MRI Zn 2+ -responsive probes Abstract : A bioinspired probe based on a zinc finger peptide functionalized by a lanthanide(iii )-DOTA monoamide complex turns out to be active for both luminescence and MRI detection of Zn 2+, depending on the lanthanide cation. A mechanism for MRI-based detection is proposed.